Efeitos da tens sobre a atividade do nervo ciático de ratos com uso de sertralina e suas implicações cardiorespiratórias - Santuzzi, Cíntia Helena (2009)
Analgesia induced by transcutaneous electrical nerve stimulation (TENS), occurs by activation of large-fibres; however, the mechanism of TENS analgesia is also related to the release of endogenous peptides and monoamines, including serotonin. Thus, this study aimed to investigate the mechanisms of high and low frequency TENS’ peripheral analgesia in rats treated with sertraline, an selective serotonin reuptake inhibitors - SSRIs, and their implications in cardiorespiratory parameters and the threshold of sensory excitation as an integral factor in the response to noxious stimulation. Male Wistar rats (n=48) weighing 250-300g were divided into six groups. The animals were treated with sertraline (3 mg/kg for 7 consecutive days) or saline. For surgical procedures the rats were anesthetized with urethane (1.2 g/kg, iv) after induction by halothane, then the femoral vein and artery were catheterized for administration of anesthetic and records of mean blood pressure (BP) and heart rate (HR) respectively. Besides it, animals were submitted to tracheostomy to record respiratory frequency (RF). Incision was made in the posterior thigh to allow access to the branching of the sciatic nerve, the proximal portion was cut completely to allow the registration of the portion of the sensory nerve, after the nerve was dissected to record their activity (NCA). After stabilization of all parameters formalin was applied in the paw (50µl, 5%) associated with high-TENS (130Hz) or low -TENS (10Hz) for 20 minutes with sensory intensity (130-µs). Data were collected at times: baseline, 10, 20, 30 and 50 minutes after the injection of formalin. Throughout the experiment, the animal's body temperature was maintained at 37 ± 0.5 ° C. The results are presented as mean ± SEM, p <0.05. The results show a significant decrease in the NCA in rats that received TENS both high-and low-frequency, and treatment with sertraline showed the same pattern as TENS; however treatment with sertraline alone was also analgesic; Noxious stimulation showed an increase in HR, MAP and RF cardiorespiratory parameters and both high and low frequency TENS was able to reverse this elevation.Treatment with sertraline demonstrated unique answers for the different TENS’ modalities of application and pain stimulus. Therefore, we conclude that the analgesic effect of TENS is also related to the activation or potentiation of peripheral endogenous opioid system and it appears that sertraline does not improve the response pattern of TENS, however sertraline alone promotes analgesic effect. As for cardiorespiratory parameters, TENS was effective in reversing the high cardiorespiratory responses promoted by the painful stimulus, demonstrating that TENS an analgesic tool capable of reversing the physiological response to pain. However, the chronic treatment with sertraline exerted changes in cardiorespiratory parameters, possibly through the activation of different subtypes of serotonin receptors in different locations in the brain.